Information and context matter: debiasing the disposition effect with lasting impact - Huang, Lingxi; Guenther, Benno (Frontiers in Behavioral Economics, 2024)
The disposition effect is one of the most prominent and widely studied behavioral biases observed among investors. It describes the tendency to close out winning investments prematurely while holding on to losing ones for too long and is generally associated with reduced investment returns. Researchers have explored various debiasing strategies and interventions to mitigate the disposition effect and its detrimental impact on returns. We summarize a between-subject experiment with n = 132 UK participants testing the impact of an informational feedback-like intervention to mitigate the disposition effect, informing participants about the disposition effect. Moreover, we re-examine our intervention's impact in the follow-up measurements which are two weeks and again three months after the first measurement. We find our intervention to have a significant impact, reducing the disposition effect in the first measurement. In addition, we still find a significant impact of the intervention, reducing the disposition effect after two weeks, while no significant impact is observed at the three-month point.While we find a higher disposition effect to be associated with lower returns for one measurement, the opposite is true for the other two measurements. Moreover, the intervention had a return reducing impact for one measurement and no significant impact for the other two. Overall, our study shows a promising intervention that may be readily deployed among retail investors with a somewhat lasting impact to mitigate the disposition effect. However, our study also shows that the relationship between the disposition effect and investment returns is nuanced.